Women of exile: German-Jewish autobiographies since 1933 - Lixl-Purcell, Andreas (Contributions in women's studies, 1988)
Verlagsinfo: Lixl-Purcell has chosen twenty-six from the hundreds of unpublished memoirs he researched. They are arranged in three sections - Persecution and Displacement, Exile and War, and Exile in Hindsight. Much of the power of their stories lies in their matter-of-fact and straightforward telling of their fears, narrow escapes, sorrows, and triumphs. There are narratives describing women's social, cultural and political networks before and after immigration, the isoilated struggles of individuals, their work as legal or illegal aliens abroad, and their involvement with underground resistance movements. American Library Book Review. Women's exile autobiographies, written usually for an audience of relatives and fellow travellers, are rarely made available to the public. This is particularly true for Jewish women who fled Germany after Hitler's rise to power in 1933. In this unusual volume, the memoirs, diaries, and letters of twenty-six of these extraordinary women are published together for the first time. Their recollections paint a provocative profile of exile life and cover a broad spectrum of emigre history on every continent. While each memoir voices an intensely personal explanation, their combined effect is to launch a radical reinterpretation of women's roles, fates, and destinies.